The Relationship Between Inflation and Trade Openness: Evidence from Ghana - Evans Yeboah; Alexander Amo Baffour (Köz-gazdaság)
The correlation between economic growth, trade openness, and inflation has been extensively studied over the years, yielding varied outcomes. Recent disruptions caused by events such as the COVID-19 pandemic and the Russia-Ukraine war have significantly affected the global economy, resulting in a notable increase in inflation rates, particularly in developing countries. This study investigates the impacts of trade openness and inflation on the Ghanaian economy from 1990 to 2022. Employing the Autoregressive Distributed Lag (ARDL) bounds testing for cointegration and the Granger causality test for empirical analysis, the study reveals a mixed short-term effect, showing both positive and negative impacts of trade openness and inflation on economic growth in Ghana. While no long-term effect of trade openness is observed, inflation is found to have a negative long-term influence on growth. Additionally, the results of the Granger causality test suggest a unidirectional causal relationship between trade openness and economic development.